Computational study of supersonic flow past non-stationary obstructions part-II-moving protrusion - Deshpande V.; Eshpuniyani B.; Sanghi S. (My University, 2025)
For an upward moving protrusion, recirculation regions develop on both sides with separation/reattachment distances increasing with protrusion height while being smaller than the corresponding fixed protrusion values. Differences in upstream wall pressures between moving versus fixed protrusions are reasoned in terms of: 1) extent of coalescence of upstream travelling compression waves into a shock; 2) inclination of this shock wave with free stream; 3) a low velocity high pressure band of fluid formed adjacent to the protrusion fore surface. Downstream wall pressures are lower than the corresponding fixed protrusion values due to a higher expansion of the flow for the range of protrusion heights considered. For an oscillating protrusion, wall pressure response to varying protrusion heights displays a hysteretic behaviour. Compressive/expansive effects generated during the protrusion's upward/downward motions persist after the protrusion changes its direction. Higher upstream and lower downstream wall pressures are observed in general at higher protrusion velocities. Copyright © 2015 Inderscience Enterprises Ltd.